An experimental study on cracking and deformations of tensile concrete elements reinforced with multiple GFRP bars. (1st October 2018) - Gribniak, Viktor; Rimkus, Arvydas; Torres, Lluis; Hui, David
Abstract: Although different setups have been developed for analysis of the serviceability properties (cracking and deformations) of reinforced concrete elements, tensile tests are remaining the most often used testing layouts. Recent studies, however, have revealed noticeable limitations of the traditional tests of concrete prisms reinforced with a centre bar. The essential aspect responsible for adequate interpretation of the test outcomes could be addressed to inter-correlation of the basic cross-section parameters, i.e. bar diameter, reinforcement ratio, and cover depth. Furthermore, the test equipment has a limited possibility comparing outcomes of the tensile prisms reinforced with bars made of steel and fibre reinforced polymer materials. To solve these problems, a special equipment for the anchorage of multiple bars has been developed. This manuscript presents and discusses the tests results of 16 prismatic specimens reinforced with steel and glass fibre reinforced polymer (GFRP) bars provided by different producers. At the same deformation range of reinforcement, almost identical crack distances are characteristic of the prisms reinforced with steel and GFRP bars with similar axial stiffness. This result enables formulating a hypothesis that crack spacing in tensile elements of equivalent axial stiffness is predominantly dependent on geometry of the concrete and, particularly, on the cover depth.